Fatal errors; or Poor Mary-Anne a tale of the last century - Lanfear, Elizabeth Hays.; Whelan, Timothy D.; James, Felicity, 1978- (London : Routledge, 2020)
In December 2015 a novel by Elizabeth Hays (c. 1765-1825) that has eluded scholars of women novelists of the 1790s for more than a century was finally discovered in the British Library. Fatal Errors was written in the late 1790s by the sister of Mary Hays, but not published until 1819 under her married name, Lanfear, and has therefore been completely overlooked until now. There has been considerable interest in the missing novel, since we know that Mary Wollstonecraft read and commented on a version of the manuscript in 1796, but it was presumed never to have been published. Now this missing piece of the conversation of the Hays-Wollstonecraft-Godwin circle has been located this modern critical edition of Fatal Errors contributes both to our knowledge of this network of radical writers and thinkers, and to our understanding of the trajectory of women's fiction and the Jacobin novel.
2. Elizabeth Hays, Chelmsford, Essex, to Mary Hays, 22 Hatton Street [Hatton garden], Holborn, 4 February 18013. Elizabeth Hays, Ingatestone, Essex, to Mary Hays, George Row [9 St. George's Place], Camberwell, 14 August 1803; Notes
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY COLLECTIONS / General; LITERARY CRITICISM / General; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Young women -- Conduct of life -- Fiction